Optical Transmission Through Strongly Coupled Gold Nanoparticle Arrays with Structural Defects (Journal of Atomic and Molecular Sciences, 2021)
We present a strongly coupled gold nanoparticle arrays with planar defect structures and numerically investigate its the transmission properties We show that two kinds of distinct resonant modes, the plasmonic resonant mode and the defect mode, appear in the forbidden photonic band gap. It is found that the plasmonic resonant mode can be controlled by introducing the planar defect, while the peak value and the width of the defect mode depend strongly on the defect distance.
Keywords: structural defect; transmission spectra; plasmonic resonant mode; defect mode.